Pengembangan Media Pembelajaran Arabic Corner Mumtāz untuk Meningkatkan Penguasaan Mufradāt Kelas XI Agama 2 MAN 3 Bantul - Syarifah; Ahmad Rodli (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2019)
Abstract This study aims to develop learning media Mumtāz Arabic Corner in increasing students’ mastery of mufrādāt and how the influence of media in the eleventh-grade students majoring in religion at MAN 3 Bantul. This study uses research and development. model. The research result of the development of Arabic learning media is in the form of learning media Mumtāz Arabic Corner. Based on the assessment of media experts on this learning media, the overall score is 55 out of the highest score of 60 and has a